2012
DOI: 10.1007/s11136-012-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between post-traumatic stress disorder symptoms and the quality of life among Wenchuan earthquake survivors: the role of social support as a moderator

Abstract: Subjective support and support availability are more useful strategies to improve the QOL of the earthquake survivors with PTSD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 36 publications
4
37
0
2
Order By: Relevance
“…We also found further evidence of the positive effect of perceived social support on the women’s happiness one and 4 years after the storm when examining the long-term determinants of the women’s happiness, which suggest that that social support is an important element for the recovery of victims of natural disasters. Similar results have been reported by other studies that have documented the protective effect of social support on exposure to Hurricane Katrina (Lowe et al 2010), and on the quality of life of survivors of earthquakes occurred in Iran (Ardalan et al 2011) and China (Lin et al 2002; Wang et al 2000; Zhao et al 2013). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found further evidence of the positive effect of perceived social support on the women’s happiness one and 4 years after the storm when examining the long-term determinants of the women’s happiness, which suggest that that social support is an important element for the recovery of victims of natural disasters. Similar results have been reported by other studies that have documented the protective effect of social support on exposure to Hurricane Katrina (Lowe et al 2010), and on the quality of life of survivors of earthquakes occurred in Iran (Ardalan et al 2011) and China (Lin et al 2002; Wang et al 2000; Zhao et al 2013). …”
Section: Discussionsupporting
confidence: 90%
“…In addition, a recent study on the association between post-traumatic stress disorder and the quality of life among Wenchuan earthquake survivors found that perceived social support weakened the negative effect of PTSD on the quality of life of the survivors 1 year after the disaster (Zhao et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Symptom severity is a robust and reliable predictor of service utilization (37-43), and is also highly correlated with social support (10-12, 44). In National Guard soldiers, greater psychiatric medication usage was related to both reduced postdeployment social support and greater PTSD severity (19).…”
Section: Discussionmentioning
confidence: 99%
“…In assessing the potential barriers and facilitators of treatment engagement, social support has emerged as a potentially important factor (4). Lack of social support is associated with an increased likelihood of developing PTSD after a traumatic event (5-9) and greater severity of PTSD among those with the disorder (10-12). However, the collected findings on the relationship between social support and mental health care engagement are equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…The association between poor QOL and earthquake-induced post-traumatic stress disorder (PTSD) has been widely investigated in recent literature [8,11]. People’s well-being after loss resulting from an earthquake is currently a concern in countries exposed to natural disasters both for public health reasons and for the economical sustainability of specific interventions [12,13].…”
Section: Introductionmentioning
confidence: 99%